PENGARUH PEMAHAMAN MATEMATIKA TERHADAP KEMAMPUAN KONEKSI MATEMATIKA SISWA KELAS VII SEMESTER GENAP SMP NEGERI 2 KASOKANDEL KABUPATEN MAJALENGKA - Hadi Kusmanto; iis marliyana (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2014)
This research aims to: 1) determine the mathematical comprehension of class VII Kasokandel Junior High School 2 Kasokandel, 2) determine the ability of mathematics connection class VII Kasokandel Junior High School 2 Kasokandel, and 3) determine how much influence the mathematical comprehension of the mathematical connection capability class VII Junior High School 2 Kasokandel. The variables measured in this study include the independent variable is the comprehension of mathematics, as well as variables related to an ability to connect math class VII Junior High School 2 Kasokandel bounded on kogntif aspects. Research methods using quantitative methods. Desian research used in this study is the One Shot model, ie a model approach that uses one-time collection of data at a time. The population in this study were all students of class VII totaling 163 students. Sampling was conducted using cluster random sampling technique that researchers randomly assigned to take one class from some existing class. Methods of data collection in this study using a test instrument. Data analysis techniques with Analyisis regression. The results showed that (1) the value of sig. (l-tailed) = 0.00 <0.05 indicates that there is a significant effect. (2) the valuet_hitung> t_tabel 3.981> 2.056, then 0 is rejected, it can be concluded that there aresignificant mathematical comprehension of the mathematical connection capabilities. (3)based on the results of hypothesis testing, it can be concluded that the comprehension of mathematics has an influence on the ability to connect math class VII junior high school 2Kasokandel, has a coefficient of determination (R Square) of 37.9% with a regression equation of Y = 36,713 + 0,485X, stating that each additional comprehension ofmathematics will affect the improvement of connections capabilities of 0.485 students math. Keywords: Comprehension of mathematics, mathematical connections